The Effect of Ability, Motivation, and Opportunity Factors on the Success of Technology Innovations Moderated by Corporate Entrepreneurial Climate - Yasinta Nikita Titisari (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
There are four main implementation issues that most companies do not recognize or respond effectively. These problems can be described in the form of a lack of understanding of what type of innovation is being sought, lack of coordination of managerial roles, not being fully effective in using operational controls, and not carrying out individual training and preparation properly. Effective recognition and response to these four issues can represent the difference between companies that are able to implement successful corporate innovation strategies and those are not. Based on the problems above, there is an urgency to conduct research regarding the role of AMO (Ability, Motivation, Opportunity) on technological innovation and the role of Corporate Entrepreneurial Climate in the implementation of successful technological innovation in a company engaged in the manufacturing industry. This study uses positivism quantitative methods in data processing and questionnaires are arranged based on 5 variables in data collection. The final result of this study found that abilities moderated by the corporate entrepreneurship climate factor had a positive influence on the success of technological innovation, motivation moderated by the corporate entrepreneurship climate factor turned out to have a negative influence on the success of technological innovation, and motivation moderated by the corporate entrepreneurship climate factor. also has a negative influence on the success of technological innovations.